Diseño de un centro de desarrollo comunitario, para la regeneración urbana de un sector en transformación: barrios Chorlaví y Moras de San Antonio de Ibarra - Almeida Navarrete, Pablo Alejandro (2023)
The titling work is carried out in the parish of San Antonio de Ibarra, province of Imbabura, which takes into account the northern zone caused by the E-35 road division, focusing on a design of a Community Development Center helping production and economy of the sector. Through theoretical and regulatory analysis, the orientation of the approach will be extended: urban, architectural, social and productive to equip the provision of services that will help the Chorlaví and Moras neighborhoods get ahead, in addition to trying to naturalize the spaces, improving habitability of public spaces. On the macro scale, it is intended to create an 'Integrative Network of existing public spaces and proposals to improve habitability and achieve universal and inclusive mobility. At the meso scale, it is proposed to improve mobility at the neighborhood level, solving the deficits of public spaces and at the micro scale, it is intended to design a Community Development Center that is oriented towards enhancing productivity, discovering spaces suitable for training, production, exhibition and commercialization of wooden products.